Colombian Biodiversity, an Opportunity for the Strengthening of the Pharmaceutical and Cosmetic Industries (2016)
ABSTRACT: Colombia, a country privileged by nature, where diversity of climates are created by large altitude gradients which generate a variety of ecosystems and beautiful badlands, punas, mountain forests, dry valleys, high deserts and salt flats; landscapes that have diversity of plants and animals and we are cata- loged as one of the countries as the greatest diversity in the world, preceded by Brazil and followed by Indonesia, China and Mexico. We have 28.000 plants and lichens; it is an invaluable heritage that can give to our country competitive advantages in the discovery and development of active ingredients for the pharmaceutical and cosmetic industry by sustainable use of our biodiversity.